Mechanical Properties of Concrete with Sintered Fly Ash Aggregate as Substitute of Natural Fine Aggregate. Issue 1 (November 2020) - Basa, Bidyadhar; Pradhan, Nibedita; Priyadarshini Parhi, Lipsita
Abstract: Attempts have been made from time long to develop construction materials which should be strong, durable and simultaneously of light weight. In an attempt to reduce the self-weight of the structural concrete, light weight aggregates are being used and implemented. Fly ash is a waste material of coal based thermal power plants. Presently, fly ash is being used in construction industries in different ways. Sintered fly ash aggregates when used as a substitute for natural aggregates benefits the preservation of natural aggregates as well as the utilization of fly ash which poses a great environmental problem for its disposal. Simultaneously, it also reduces the cost of concrete. In the present investigation, sintered fly ash light weight aggregates have been used as a partial replacement of natural sand as fine aggregate in concrete. Varying percentages of natural fine aggregate have been replaced by sintered fly ash light weight aggregates. Experimental investigations have been carried out to study the mechanical properties related to the strength of concrete, namely, compressive strength, split tensile strength and flexural strength with sintered fly ash aggregate as fine aggregate substitute in concrete. In all mixes, silica fume have been used in conjunction with the binder material consisting of ordinary Portland cement.